PROSPECTS FOR AGRICULTURAL BUSINESS DEVELOPMENT IN IMERETI REGION (Globalization and Business, 2023)
The development of agribusiness in Georgia is quite promising and realistic. Imereti region is one of the most distinguished regions in Georgia in terms of agricultural production. Imereti region has been involved in the production and sales of agricultural products for a long time (e.g. grapes, tea, cheese, herbs, cucumbers, tomatoes, etc.) that have been widely popular throughout the country.  The research has shown that various products produced in Imereti region (especially: cucumbers, tomatoes, herbs, wine, cheese, tea) are quite in demand in the hotel food service, however, there is still no adequate supply of hotels with the products produced in Imereti region.